Comparison of the Effectiveness of Emotion-Focused Therapy and Intensive Short-Term Psychodynamic Therapy on Sexual Dysfunction and Quality of Sexual Life in Women - Mirzaei, Amir; Sharifi, Tayebeh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to compare the effectiveness of emotion-focused therapy and short-term psychodynamic therapy on sexual dysfunction and the quality of sexual life in women attending counseling and psychotherapy centers in Isfahan. Methods: The research design was a quasi-experimental pre-test, post-test, and follow-up. The population included all women in Isfahan province suffering from sexual dysfunction in 2023. Sixty individuals were selected through purposive sampling and randomly assigned into three groups: twenty in the first experimental group, twenty in the second experimental group, and twenty in the control group. The first experimental group underwent emotion-focused psychological intervention based on the therapeutic protocol by Gilbert (2014) in fifteen 60-minute sessions, and the second experimental group received short-term psychodynamic psychological intervention based on the therapeutic protocol (Davanloo, 2013) in twelve 60-minute sessions held weekly, followed by a one-month follow-up. The control group was placed on a two-month waiting list for the most effective intervention. Data collection for analysis was conducted using the Rosen et al. (2000) Women’s Sexual Dysfunction Questionnaire and the Simonds et al. (2005) Women’s Sexual Life Quality Questionnaire. Data analysis was performed using mixed ANOVA with SPSS version 25. Findings: The findings indicated that both treatments were effective in reducing sexual dysfunction in women (F = 73.08, p < .001) and improving the quality of sexual life (F = 18.02, p < .001). However, there was a significant difference between the effectiveness of the two therapeutic methods in reducing sexual dysfunction and increasing the quality of sexual life in women (p < .001). Conclusion: It can be concluded that both emotion-focused and short-term psychodynamic therapies are effective in reducing sexual dysfunction and improving the quality of sexual life in women. Both treatments can be used to reduce psychological issues in women attending counseling centers.